2000
DOI: 10.1034/j.1600-0706.2000.880216.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant phenology, nutrients and herbivory on growth and defensive chemistry of plantain, Plantago lanceolata

Abstract: 2000. Effects of plant phenology, nutrients and herbivory on growth and defensive chemistry of plantain, Plantago lanceolata. -Oikos 88: 371 -379.To assess the combined effect of herbivory, nutrient availability and plant phenology on plant mass and defensive chemistry, we conducted a field experiment with plantain (Plantago lanceolata: Plantaginaceae) using three levels of herbivory, three levels of fertilizer and two harvest dates. Shoot mass of the no-herbivory plants showed a nonlinear response to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 31 publications
(39 reference statements)
2
32
3
1
Order By: Relevance
“…High constitutive levels of iridoid glycosides in plants associated with S. calospora may be a result of early induction by the infection of a fungus that does not benefit growth in the long term, resulting in a stress response to limited resources (Bennett and Bever 2007;Bever 2002a), a strategy to counter herbivory in a nonoptimal environment, or a response to increased nitrogen in plant tissues. Although increased nutrients result in decreased concentrations of iridoid glycosides in P. lanceolata tissues (Jarzomski et al 2000), nutrient concentrations are not likely responsible for the increased iridoid glycosides in plants associated with S. calospora because they had an intermediate amount of nitrogen in tissues (Fig. 3).…”
Section: S Calosporamentioning
confidence: 92%
See 1 more Smart Citation
“…High constitutive levels of iridoid glycosides in plants associated with S. calospora may be a result of early induction by the infection of a fungus that does not benefit growth in the long term, resulting in a stress response to limited resources (Bennett and Bever 2007;Bever 2002a), a strategy to counter herbivory in a nonoptimal environment, or a response to increased nitrogen in plant tissues. Although increased nutrients result in decreased concentrations of iridoid glycosides in P. lanceolata tissues (Jarzomski et al 2000), nutrient concentrations are not likely responsible for the increased iridoid glycosides in plants associated with S. calospora because they had an intermediate amount of nitrogen in tissues (Fig. 3).…”
Section: S Calosporamentioning
confidence: 92%
“…In previous studies of P. lanceolata inducible responses (Adler et al 1995;Bowers and Stamp 1993;Darrow and Bowers 1999;Fuchs and Bowers 2004;Jarzomski et al 2000;Stamp and Bowers 1994 there was often greater induction of iridoid glycosides in plants likely lacking AM fungi (e.g., in greenhouses) versus environments where AM fungi are likely present (e.g., field settings). While many factors may be responsible for the differences in induction observed between greenhouse and field studies, this result is consistent with our observation that the presence of multiple AM fungal species reduces the induced response in P. lanceolata, and may suggest that in environments where AM fungi are common, defense strategies other than induced chemical responses are likely to be important.…”
Section: S Calosporamentioning
confidence: 93%
“…Past experiments on target metabolite induction in Plantago have found induction to be short‐lived and therefore difficult to detect (i.e., Bowers & Stamp, 1993; Darrow & Bowers, 1999; Fuchs & Bowers, 2004). The timing of the metabolomic screening in our study, as well as in other studies where no or insignificant differences were found (i.e., Jarzomski et al., 2000; Stamp & Bowers, 1996; Sutter & Muller, 2011), could limit detection of induced metabolites. Additional work should aim to investigate important factors such as the time and type of herbivore damage under in situ conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Plant phenology vary among and within years and can affect the insect herbivores directly by synchronism between specifi c phenological stages and population dynamics of insects (How et al 1993 ;Fox et al 1997 ;Vitou et al 2008 ) or indirectly, by determining the quality of plant tissues for herbivores (Jarzomski et al 2000 ;Russel and Louda 2004 ;Coyle et al 2010 ). Moreover, the supra annual phenology also produces variation in resource for herbivores between years of high and low plant reproduction (Obeso 2002 ;Forister 2005 ;Fagundes et al 2013 ).…”
Section: Marcilio Fagundesmentioning
confidence: 94%